Live Donor Renal Transplant with Simultaneous Bilateral Nephrectomy for Autosomal Dominant Polycystic Kidney Disease (APKD) is Feasible and Satisfactory at Long Term Follow-Up - Ahmad, Sarwat B. (Transplantation, 2016)
BACKGROUND: Timing of BN is controversial in patients with refractory symptoms of autosomal dominant polycystic kidney disease (APKD) in need of a renal transplant. METHODS: Adults who underwent LRT+SBN from August 2003–2013 at a single transplant center (n=66) were retrospectively compared to a matched group of APKD patients who underwent LRT alone (n=52). All patients received general health and polycystic kidney symptom surveys. RESULTS: SBN increased operative duration, EBL, transfusions, IV fluid, and hospital length of stay. Most common indications for BN were pain, loss of abdominal domain, and early satiety. There were more intraoperative complications for LRT+SBN (6 vs. 0, p=0.03; 2 vascular, 2 splenic, and 1 liver injury; 1 re-exploration to adjust graft positioning). There were no differences in Clavien-Dindo grade I or II (39% vs. 25%, p=0.12) or grade III or IV (7.5% vs. 5.7%, p=1.0) complications during the hospital course. There were no surgery related mortalities. There were no differences in readmission rates (68% vs. 48%, p=0.19) or readmissions requiring procedures (25% vs. 20%, p=0.51) over 12 months. 100% of LRT+SBN allografts functioned at >1 year for those available for follow-up. Survey response rate was 40% for LRT-alone and 56% for LRT+SBN. 100% of LRT+SBN survey responders were satisfied with their choice of having BN done simultaneously. CONCLUSIONS: Excellent outcomes for graft survival, satisfaction, and morbidity suggest that the combined operative approach be preferred for patients with symptomatic APKD to avoid multiple procedures, dialysis, and costs of staged operations.